A Comparison Study of Fiber Diameter's Effect on Characteristic Features of Donepezil/Curcumin-Loaded Polycaprolactone/Polylactic Acid Nanofibers - EKENTOK ATICI, CEYDA; GÜNDÜZ, OĞUZHAN; ÇAM, MUHAMMET EMİN; TATAR, ESRA; YAVUZ, AYŞE NUR (My University, 2022)
Nanofibers (NFs) offer an alternative option for the treatment of Alzheimer\"s disease (AD) by addressing unmet clinical problems. In this study, anti-AD drugs, donepezil (DO) and curcumin (CUR), are loaded in polylactic acid/polycaprolactone NFs. The effect of fiber diameter on drug release behavior is mainly observed, and the successful loading of DO and CUR to NFs is demonstrated. The tensile strength of DO/CUR-loaded NFs (DNFs) with lower fiber diameter is found to be higher. The working temperature is increased by the decrease of glass transition temperature and increase of the melting temperature after loading drugs. Furthermore, the increase in the percentage of swelling and decrease in the degradation rate for NFs are observed due to the increase of fiber diameter. Encapsulation efficiency and burst release percentages for DNFs are augmented by the increase of fiber diameter. Nevertheless, DNFs exhibit a sustained drug release manner over 2 weeks. NFs do not demonstrate a toxic effect on L929 (mouse fibroblast) cells, and additionally, they promote cell proliferation. Considering all these results, it is proven that the fiber diameter affects all characteristic features of NFs, and DNFs lead to a new and promising drug delivery system for the treatment of AD.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); POLİMER BİLİMİ; Temel Bilimler (SCI); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); POLYMER SCIENCE; CHEMISTRY; Natural Sciences (SCI); Metals and Alloys; Materials Chemistry; Polymers and Plastics; Chemistry (miscellaneous); General Materials Science; General Chemistry; Physical Sciences; Alzheimer's disease; curcumin; donepezil hydrochloride; electrospinning; nanofibers; IN-VITRO; ELECTROSPUN NANOFIBERS; ALZHEIMERS-DISEASE; SUSTAINED-RELEASE; DRUG-RELEASE; DELIVERY; CURCUMIN; MICROSPHERES; TETRACYCLINE; DEGRADATION